Development of Learning Domino Card Learning Media to Improve Social Science Learning Outcomes - Radya Nasyawa; Sri Sami Asih (Jurnal Penelitian Pendidikan IPA, 2025)
Based on the results of the pre-research, problems were found in the form of the lack of use of learning media and the development of learning resources only through student books and teacher books at SDN Mangkang Wetan 03 Semarang City so that it affects the low learning outcomes of students. This study aims to develop, test the feasibility and effectiveness of the learning media Domino Learning Card. This study uses research and development (R&D) research that refers to the Borg and Gall model. The population in this study amounted to 27 students with 6 small-scale test subjects and 21 large-scale subjects in grade IV students of SDN Mangkang Wetan 03 Semarang City. The data collection techniques used are tests (pretest-posttest) and non-tests in the form of observations, interviews, document studies and questionnaires. The results of validation by media experts and material experts show that the Domino Card Learning media meets the criteria very feasible. Based on the results of the prestest and posttest , it is known that the Domino Learning Card media is effective in improving student learning outcomes, shown by the N-Gain test result of 0.7037 which is in the high and effective category. From these results, it can be concluded that the learning media Domino Card Learning is very feasible and effective to improve student learning outcomes in learning science and plant body parts material in grade IV SDN Mangkang Wetan 03 Semarang City.